When books went to war [book club bag] : the stories that helped us win World War II - Manning, Molly Guptill, 1980- (Houghton Mifflin Harcourt, 2014)
Chronicles the joint effort of the U.S. government, the publishing industry, and the nation's librarians to boost troop morale during World War II by shipping more than one hundred million books to the front lines for soldiers to read during what little downtime they had.